INNOVATIVE FINANCING SCHEMES FOR AGRICULTURAL INFRASTRUCTURE: OVERCOMING LOCAL FISCAL CONSTRAINTS THROUGH INTER-GOVERNMENTAL COLLABORATION (A CASE STUDY OF BIREUEN REGENCY) - Syamsil Adri (STAI Nusantara Kota Banda Aceh, 2026)
Abstract Achieving food self-sufficiency in Bireuen Regency currently faces a severe policy deadlock. Following the late-2025 floods, 4,731 hectares of productive rice fields and vital infrastructure, such as the Pante Lhong and Hagu Peudada dams, suffered massive damage. The root cause is a local fiscal